Pembelajaran Tarikh Berbasis Kearifan Lokal Pada Kelas IX di SMP Muhammadiyah 3 Yogyakarta - Lussita Jeni Nindika; Fajar Rachmadhani (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2020)
This study aims to analyze: (1) the implementation of Tarikh (history) learning based on local wisdom, (2) the supporting and inhibiting factors of Tarikh learning based on local wisdom in Class IX at SMP (Junior High School) Muhammadiyah 3 Yogyakarta The type of this research approach is a descriptive qualitative approach. The subjects of this research were the activities of teachers and students during the Tarikh learning process. The object of this research was local wisdom in Tarikh learning method in Class IX at SMP Muhammadiyah 3 Yogyakarta. Data were obtained through observation of learning activities, interviews, field notes, and documentation in the form of pictures of learning activities. Data analysis techniques included the stages of data reduction, data presentation, and conclusion. The validity of the data was obtained through triangulation. The results of this study indicate things as follows: (1) the implementation of Tarikh learning in Class IX at SMP Muhammadiyah 3 Yogyakarta is in accordance with the local wisdom of the Special Region of Yogyakarta, (2) the supporting factors for the implementation of Tarikh learning based on local wisdom in Class IX at SMP Muhammadiyah 3 Yogyakarta are adequate learning facility and students’ awareness of the importance of preserving history and culture, while the inhibiting factors for implementing Tarikh learning based on local wisdom in Class IX at SMP Muhammadiyah 3 Yogyakarta are classroom atmosphere, the number of subject matter, and the lack of student motivation.